2020
DOI: 10.21203/rs.3.rs-55527/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of inoculated gut bacteria on the development of Bactrocera dorsalis and on its susceptibility to the entomopathogenic fungus, Metarhizium anisopliae

Abstract: Background: Symbiotic interactions between insects and bacteria have been associated with a vast variety of physiological, ecological and evolutionary consequences for the host. A wide range of bacterial communities have been found in association with the oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae), an important pest of cultivated fruit in most regions of the world. We evaluated the diversity of gut bacteria in B. dorsalis specimens from several populations in Kenya and investigated… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
(75 reference statements)
1
3
0
Order By: Relevance
“…Similar to earlier microbiome reports from tephritids [10,17,27, 28], we found that, Proteobacteria and Firmicutes were the most abundant bacterial phyla in B. dorsalis larvae. This nding suggests the intimate association between B. dorsalis and these phyla, and that they could be contributing to the physiological functioning of this pest such as development and nutrient digestion among others.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to earlier microbiome reports from tephritids [10,17,27, 28], we found that, Proteobacteria and Firmicutes were the most abundant bacterial phyla in B. dorsalis larvae. This nding suggests the intimate association between B. dorsalis and these phyla, and that they could be contributing to the physiological functioning of this pest such as development and nutrient digestion among others.…”
Section: Discussionsupporting
confidence: 91%
“…This nding suggests the intimate association between B. dorsalis and these phyla, and that they could be contributing to the physiological functioning of this pest such as development and nutrient digestion among others. Earlier studies [16,17,19,21,29] investigating Proteobacteria and Firmicutes bacterial strains and their roles in the eco-physiological functions of B. dorsalis con rm this phenomenon.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations